COPA Syndrome—From Pathogenesis to Treatment - Vlad Padureanu; Mircea-Cătălin Forțofoiu; Ionut Donoiu; Eugen-Nicolae Tieranu; Catalin Dumitrascu; Rodica Padureanu; Anca Emanuela Mușetescu; Cristina Alexandru; Carmen Catalina Iorgus; Florin Bobirca; Ana Dascalu; Anca Bobirca (Diagnostics)
Coatomer subunit α (COPA) syndrome is a mendelian autosomal dominant immune dysregulation disease characterized by early onset lung disease in the form of diffuse alveolar hemorrhaging or interstitial lung disease, frequently associated with arthritis, glomerulonephritis, and high titer autoantibodies usually mimicking other autoimmune diseases. While immunosuppressive medication has been effective in controlling arthritis, data on long-term lung disease control remains scarce, which poses a real challenge as the progression of lung disease is the main cause of poor life expectancy in COPA patients. Nevertheless, JAK inhibitor therapy seems to be the most promising therapeutic choice now.